Selectively Targeted Anti-Neoplastic Cytotoxicity of Three Immunopharmaceuticals with Covalently Bound Fludarabine, Gemcitabine and Dexamethasone Moieties Synthesized Utilizing Organic Chemistry Reactions in a Multi-Stage Regimen - Coyne, Cody P.; Narayanan, Lakshmi (Current Pharmaceutical Design, 2018)
Background: Unintentional passive diffusion of conventional small molecular weight pharmaceuticals across intact membranes of normal healthy cells in tissues and organ systems induces sequelae that limit therapeutic dosage and duration of administration. Selective “targeted” delivery of pharmaceuticals is a molecular strategy that can potentially provide heightened margins-of-safety with greater potency and improved efficacy. Materials and Methods: Monophosphate analogs of fludarabine, gemcitabine, and dexamethasone were combined with a carbodiimide reagent in the presence of imidazole to produce reactive intermediates that were subsequently covalently bound to monoclonal anti-IGF-1R or anti-EGFR IgG-immunoglobulin. The resulting covalent immunopharmaceutical end-products, fludarabine-(5'-phosphoramidate)-[anti-IGF-1R], gemcitabine-(5'- phosphoramidate)-[anti-IGF-1R], and dexamethasone-(C21-phosphoramidate)-[anti-EGFR] were evaluated by SDS-PAGE/chemiluminescent autoradiography (fragmentation/polymerization detection), UV spectrophotometric absorbance (purity; molar-incorporation-index), cell-ELISA (retained selective binding-avidity), and cell vitality-viability (selectively “targeted” anti-neoplastic cytotoxicity). Results: Maximum selectively “targeted” anti-neoplastic cytotoxicity of fludarabine-(5'-phosphoramidate)-[anti- IGF-1R], gemcitabine-(5'-phosphoramidate)-[anti-IGF-1R], and dexamethasone-(C21-phosphoramidate)-[anti- EGFR] was detected at the pharmaceutical-equivalent concentrations of 10-5 M (94.7%), 10-7 M (93.1%), and 10-7 M (64.9%) respectively. Discussion: Organic chemistry reactions were optimized in a template multi-stage synthesis regimen for fludarabine-( 5'-phosphoramidate)-[anti-IGF-1R], gemcitabine-(5'-phosphoramidate)-[anti-IGF-1R], and dexamethasone-( C21-phosphoramidate)-[anti-EGFR]. Attributes of the synthesis regimen include; [-i-] covalent bonding of pharmaceutical moeities at high molar incorporation indexes, [-ii-] implementation of organic chemistry reactions in a non-dedicated synthesis regimen allowing component substitution and [-iii-] optional preservation of presynthesized amine-reactive pharmaceutical intermediates for on-demand immunopharmaceutical synthesis. Attributes of the covalent immunopharmaceuticals are; absence of any synthetically introduced chemical groups, retained IgG-immunoglobulin binding-avidity and potent selective “targeted” anti-neoplastic cytotoxic potency. Under in-vivo conditions, supplemental anti-neoplastic cytotoxicity is realized through trophic receptor inhibition and activation of multiple cytotoxic host immune responses.
Keywords: anti-IGF-1R